PEMBUATAN PAPAN PARTIKEL DARI SERBUK GERGAJIAN KAYU AKASIA MANGIUM (Acacia mangium) DAN KAYU SUNGKAI (Peronema canescens) MENGGUNAKAN PEREKAT RESIN POLYESTER - Agus Supriyanto; Noor Mirad Sari; Rosidah R Radam (Universitas Lambung Mangkurat, 2020)
This research was to determine the physical and mechanical properties of particle board from acacia sawdust and sawn wood sawdust. The results of water content ranged from 6.85 to 9.22%, density ranged from 0.39 to 0.47 g / cm3, thickness development ranged from 2.21 to 7.04%, flexural strength (modulus of elasticity or MOE ) ranges between 1000.33 - 16127.48 kgf / cm² and the strength of the fracture (modulus of Rupture or MOR) ranges from 1.10 - 1.73 kgf / cm². MOE and MOR values and densities in treatment C that do not meet SNI 03-2105-2006 while in testing other treatments have meet SNI 03-2105-2006. The composition of raw materials has a very significant effect on the treatment of water content, density, thickness development and MOE. Physical and mechanical properties had no significant effect on the treatment of MOR values. The physical properties of particle board on average meet ISN 03-2105-2006. There are no mechanical properties that meet SNI 03-2105-2006.Keywords: Particle board; waste; polyester resin